2022
DOI: 10.2147/nss.s348242
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Problematic Online Pornography Use, Psychological Stress, Emotion Dysregulation and Insomnia Symptoms During the COVID-19 Pandemic: A Mediation Analysis

Abstract: Purpose Although a link between problematic online pornographic use (POPU) and insomnia symptoms has been established, psychological and psychopathological mechanisms underlying this relationship are still not clear. Psychological stress and emotion dysregulation have been pointed out as relevant in the development and maintenance of insomnia. This study aims to explore the associations between POPU, psychological stress, emotion dysregulation and insomnia symptoms and to understand the mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The scientific interest in behavioural addictions is constantly evolving, with a focus not only on offline and onsite addictions such as gambling disorder [20,84] or exercise addiction [85][86][87] but also on those related to the digital world (e.g., [48,88]). Indeed, although the Internet offers numerous advantages by facilitating communications, speeding up the circulation of information, and expanding access to services, it can also become the site of some problematic and dysfunctional behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific interest in behavioural addictions is constantly evolving, with a focus not only on offline and onsite addictions such as gambling disorder [20,84] or exercise addiction [85][86][87] but also on those related to the digital world (e.g., [48,88]). Indeed, although the Internet offers numerous advantages by facilitating communications, speeding up the circulation of information, and expanding access to services, it can also become the site of some problematic and dysfunctional behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Next, this study focused on the in uence of perceived stress on online aming, which was one type of expression of online deviant behavior. Recent evidence suggested that psychological stress has a signi cant relevance on online pornography use during the COVID-19 pandemic (Musetti et al, 2022), and no studies were found that examined the relationship between perceived stress and online deceptive behavior. Therefore, future research can focus on the in uence of perceived stress on several other dimensions of online deviant behavior (including online pornography and online deception), explore the in uence of perceived stress on online deviant behavior, and further enrich theoretical and practical research on online deviant behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the effects attributed to negative emotions on conspiracy theories are due to differences in strategies for responding to and regulating affective experiences. Along these lines, emotion dysregulation has typically been associated with increased reactivity to stressful situations [ 53 , 54 ], and consequently, numerous recent studies have found that individuals who lack adaptive emotion regulation skills were particularly affected by the COVID-19 crisis [ 55 , 56 , 57 , 58 ]. It is therefore likely that individuals with high emotion dysregulation are particularly vulnerable to conspiracy theories in a climate of heightened negative affect because they have difficulty processing negative emotional experiences effectively.…”
Section: Introductionmentioning
confidence: 99%